2012
DOI: 10.1308/003588412x13373405386934
|View full text |Cite
|
Sign up to set email alerts
|

Double bypass for inoperable pancreatic malignancy at laparotomy: postoperative complications and long-term outcome

Abstract: INTRODUCTIONBetween 4% and 13% of patients with operable pancreatic malignancy are found unresectable at the time of surgery. Double bypass is a good option for fit patients but it is associated with high risk of postoperative complications. The aim of this study was to identify pre-operatively which patients undergoing double bypass are at high risk of complications and to assess their long-term outcome.METHODSOf the 576 patients undergoing pancreatic resections between 2006 and 2011, 50 patients who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
25
1
Order By: Relevance
“…Following screening of titles and abstracts, 25 papers were retrieved in full‐text form and assessed for eligibility. All 25 articles reported the effects of postoperative complications on long‐term survival; however, eight of these were of poor methodological quality as judged by a NOS score of 6 or less and were therefore excluded ( Tables S1 and S2 , supporting information). Poor NOS scores were due to inadequate or unreported follow‐up, lack of patient demographic information, and lack of appropriate controls for confounding factors (such as use of unadjusted univariable regression models).…”
Section: Resultsmentioning
confidence: 99%
“…Following screening of titles and abstracts, 25 papers were retrieved in full‐text form and assessed for eligibility. All 25 articles reported the effects of postoperative complications on long‐term survival; however, eight of these were of poor methodological quality as judged by a NOS score of 6 or less and were therefore excluded ( Tables S1 and S2 , supporting information). Poor NOS scores were due to inadequate or unreported follow‐up, lack of patient demographic information, and lack of appropriate controls for confounding factors (such as use of unadjusted univariable regression models).…”
Section: Resultsmentioning
confidence: 99%
“…13 Outcomes Table 1 shows outcomes of biliary and gastrointestinal double bypass from the literature. 4,6,7,9,10,[14][15][16][17][18][19][20][21][22] Among the 14 studies, two were prospective randomized controlled trials (RCTs) comparing double bypass and biliary bypass alone, 14,15 eight studies were retrospective comparative studies 4,7,10,[16][17][18][19][20] and the remaining were case series. 6,9,21,22 A B …”
Section: Surgical Proceduresmentioning
confidence: 99%
“…14,16,[18][19][20] Mortality rates ranged from 0% to 7%, and morbidity rates ranged from 3% to 50%. 4,6,7,9,10,[14][15][16][17][18][19][20][21][22] The morbidity rates were relatively high probably because the preoperative condition of a symptomatic patient is usually suboptimal due to medical problems caused by the disease (i.e., jaundice secondary to BO, undernourishment secondary to GOO). Furthermore, our analysis showed that prophylactic double bypass performed for unresectable pancreatic cancer patients without symptoms of BO and GOO was associated with lower morbidity rate (3%).…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…24 Hospital payments were calculated using International Classification of Diseases, 9th Revision (ICD-9), procedural and diagnosis-related group (DRG) codes. Data were extracted from Gastrojejunostomy plus hepaticojejunostomy 0.30 0.10-0.50 0.30 0.10-0.50 36,37 Gastrojejunostomy plus biliary stent 0.25 0.10-0.25 0.25 0.10-0.25…”
Section: Costsmentioning
confidence: 99%